2008
DOI: 10.1002/jae.1022
|View full text |Cite
|
Sign up to set email alerts
|

Semiparametric hedonic price models: assessing the effects of agricultural nonpoint source pollution

Abstract: In the area of environmental analysis using hedonic price models, we investigate the performance of various nonparametric and semiparametric specifications. The proposed model specifications are made up of two parts: a linear component for house characteristics and a non-(semi)parametric component representing the nonlinear influence of environmental indicators on house prices. We adopt a general-to-specific search procedure, based on recent specification tests comparing the proposed specifications with a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Our findings also agree with results obtained by Desmet (2000) for car markets and with recent empirical results by Bontemps et al (2008), obtained using a kernel-based semiparametric approach.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings also agree with results obtained by Desmet (2000) for car markets and with recent empirical results by Bontemps et al (2008), obtained using a kernel-based semiparametric approach.…”
Section: Discussionsupporting
confidence: 82%
“…However, previous research has shown that in hedonic models restrictive parametric specification can rarely be justified a priori (e.g., Cropper et al 1988;Ekeland, Heckman, andNesheim 2002, 2004) and that semi-and nonparametric alternatives can provide several advantages (Anglin and Gencay 1996;Parmeter, Henderson, and Kumbhakar 2007;Bontemps, Simioni, and Surry 2008). In addition, findings reported by Deschênes and Greenstone (2012) seem to indicate that the predicted impacts of climate change on farm profits are heavily dependent on the functional form assumed for the climatic and control variables.…”
mentioning
confidence: 70%
“…A problem with the latter techniques is that it is very data‐intensive, as most hedonic price functions contain a large number of explanatory variables. This may lead to the so‐called “curse of multidimensionality”: estimation precision rapidly deteriorates when the number of explanatory variables increases (Horowitz and Savin, 2001; Bontemps, Simoni, and Surry, 2008; McMillen, 2010)…”
Section: Hedonic Price Methods and Mixed Land Usementioning
confidence: 99%